TOTAL QUALITY MANAGEMENT IN AFFECTING COMPANY OPERATIONAL PERFORMANCE IN CONVECTION SMEs WITH ORGANIZATIONAL COMMITMENT AS A MEDIATOR - Putra, Teuku Roli Ilhamsyah; Yunus, Mukhlis; Fakhreza, Teuku Hafiz (Jurnal Aplikasi Manajemen, 2021)
This study aims to prove the role of Total Quality Management (TQM) and organizational commitment in supporting the achievement of company operational performance. The population was all Convection SMEs in the city of Banda Aceh, consisted of 294 Convection SMEs. The sample was selected using a proportional sampling technique where sampling considers elements or categories in the study population. The sample taken was 15% of the population. One respondent represented one unit of SMEs, so the sample has amounted to 169 respondents. Data was collected using questionnaires. The model was analyzed with the Structural Equation Model Analysis. The result showed an influence between TQM on Organizational Commitment, TQM on Company Operational Performance, and Organizational Commitment on Company Operational Performance. This study also found that organizational commitment can act as a partial mediator to strengthen the effect of TQM on Company operational performance. The interesting issue in this study lies in the discussion of the organizational commitment to solving the inconsistency problems in the quality of convection production in SMEs. Furthermore, the other researchers can provide more concepts and variables to enrich this research model, like other mediators for TQM to achieve performance or even the commitment that can strengthen the TQM and performance. The model also can be a reference for practitioners to set their strategy in further, to go more productive.